2020
DOI: 10.1038/s41436-020-0814-5
|View full text |Cite|
|
Sign up to set email alerts
|

Alternative mRNA splicing can attenuate the pathogenicity of presumed loss-of-function variants in BRCA2

Abstract: Purpose: Current interpretation guidelines for germline variants in high-risk cancer susceptibility genes consider predicted loss-offunction (LoF) variants, such as nonsense variants and variants in the canonical splice site sequences of BRCA2, to be associated with high cancer risk. However, some variant alleles produce alternative transcripts that encode (partially) functional protein isoforms leading to possible incorrect risk estimations. For accurate classification of variants it is therefore essential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 42 publications
(76 reference statements)
0
34
0
Order By: Relevance
“…Possibly, one could complement PALB2 KO cells containing DR-GFP with a BAC containing the full length human PALB2 gene. Such a method has previously been described for BRCA1 and BRCA2 (Kuznetsov et al, 2008;Chang et al, 2009;Mesman et al, 2018Mesman et al, , 2020 and would allow for the introduction and functional analysis of splice variants in coding and non-coding regions, further improving their classification.…”
Section: Toward the Functional Analysis Of Palb2 Vus In Rna Splicingmentioning
confidence: 99%
“…Possibly, one could complement PALB2 KO cells containing DR-GFP with a BAC containing the full length human PALB2 gene. Such a method has previously been described for BRCA1 and BRCA2 (Kuznetsov et al, 2008;Chang et al, 2009;Mesman et al, 2018Mesman et al, , 2020 and would allow for the introduction and functional analysis of splice variants in coding and non-coding regions, further improving their classification.…”
Section: Toward the Functional Analysis Of Palb2 Vus In Rna Splicingmentioning
confidence: 99%
“…More recently, BRCA2 variants were expressed in BRCA2-deficent DLD1 cells and their response to multiple PARP inhibitors (PARPi) was used to functionally classify them 18 . We and others have utilized mouse embryonic stem cells (mESC) as a model system for functional evaluation of BRCA1/2 VUS based on the observation that both genes are essential to the viability of mESC [19][20][21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent reports describe downgrading splicing variants at the ESS in BRCA1 and BRCA2 from P/LP to VUSs or B/LB because of evidence from the Evidence-based Network for the Interpretation of Germline Mutant Alleles (ENIGMA) consortium and functional studies showing that some ESS variants result in viable, functional transcript isoforms. 6,[35][36][37] In addition, two clinical laboratories recently reported discordant interpretations of an intronic variant in BRCA2. One lab classified the variant as LP because of its low prevalence, in silico predictions of splicing defects, and RNA analysis demonstrating altered splicing (but without quantification).…”
Section: Discussionmentioning
confidence: 99%
“…2 Some studies have revealed previously unrecognized variety in RNA transcript isoforms associated with well-studied genes, including BRCA1 (MIM: 113705) and BRCA2 (MIM: 600185), showing that our understanding of naturally occurring alternative splicing of disease gene transcripts is still evolving. [3][4][5][6] Recent studies have also illuminated how differential expression of transcript isoforms can influence whether certain sequence variants are tolerated. 7,8 As a result of this underappreciated complexity, variants that allow biologically viable alternative splicing may be incorrectly classified as disease causing.…”
Section: Introductionmentioning
confidence: 99%